Rizqi Car Rental Booking System Based on Mobile Applications - Alid, Nur Suhana; Aziz, Ruhaya (Applied Information Technology And Computer Science, 2021)
Rizqi Car Rental Booking System based on Mobile Application developed to enable customers to book rental cars online that can provide a wealth of information related to car rental reservations. In addition, the system was developed to facilitate the car rental information management of Rizqi Car Rental. Based on observation, this system offer a user feedback module compare to the existing system that does not offer a user feedback module. In order to make the Rizqi Car Rental Booking System based on Mobile Application, the waterfall development process model is used as a process model that acts as a guideline that covers several phases namely planning, analysis, design, and implementation. At the end of the system development, customers can make online car rental reservations that are seen to provide comfort and satisfaction to customers and help the management of Rizqi Car Rental Company booking to run smoothly.